NATURA MIARĄ SENSU KULTURY - Duma, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article the author discusses the problem of correlation between culture and nature as a condition in the justification of rationality of the former domain. The first section presents the analyses of a naturalistic position, according to which culture is reduced to the natural world, meanwhile the phenomena that could not be expressed in the language of science are only a kind of “conceptual surplus.” Afterwards the author focuses on the opposite situation, according to which the world of nature is treated nothing but as a product of culture, while the only factor determining both nature and culture is “social practices.” The consequence of these positions is the total relativization of culture. In the second part, the author provides a realistic explanation of the relationship between culture and nature, developed on the basis of the philosophy of Aristotle and St. Thomas Aquinas by a Polish philosopher Mieczysław A. Krąpiec, who referring to the metaphysical understanding of the nature of being as a principle basically determining the being to its proper action from within, has formulated the philosophical conception of culture, according to which the whole culture is rational and meaningful as exteriorizing human cognition.